Radioimmunoguided Surgery for Colorectal Cancer - An Overview - Wojciech Brzezinski; Olin G Thurston; Ernest Wiens (Canadian Journal of Gastroenterology)
Many different monoclonal antibodies used experimentally and clinically are highly tumour-specific. Radiolahelling of these antibodies has been successfully accomplished. lmmunoscintigraphy of primary and metastatic cancers has a reported sensitivity of 59 to 70%. However, in many studies, operative and histologic confirmation is lacking. Radioimmunoguided surgery is a promising new adjunctive technique for the surgical treatment of colorectal cancer. Its reported sensitivity ranges between 70 and 100% and specificity between 66 and 100%. In approximately one-third of patients wirh colorectal cancer, additional intraoperative information concerning the presence of subclinical tumours was gained using radioimmunoguided surgery. This system has the potential to assist the surgeon in performing complete resection of cancer and decrease the local recurrence rate. This could be of particular clinical importance for rectosigmoid tumours where the reported local recurrence rate is as high as 30%. Despite the advances made, many problems still need to be resolved. The important ones include: finding an antibody with high tumour specificity and at the same time rapid clearance from the blood pool and normal tissue - this would avoid the delay between monoclonal antibody injection and surgery and would make this approach more easily accepted by the patient; and use of alternative isotopes for radiolabelling. Radioimmunoguided surgery has the potential to change the way surgery for colorectal cancer is being performed. It offers the possibility of improvement in patient survival.